2010
DOI: 10.1016/j.watres.2010.07.079
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dissolved organic compounds on the photodegradation of the herbicide MCPA in aqueous solution

Abstract: This works shows that the addition of phenol and 2-propanol as model organic compounds significantly decreases the direct photolysis quantum yield of 4-chloro-2-methylphenoxyacetic acid (MCPA) upon UVB irradiation in aqueous solution. Laser flash photolysis data suggest that 2-propanol is able to decrease the formation of the MCPA excited states under irradiation. A decrease from 0.54 to 0.34 of the photolysis quantum yield of the anionic form of MCPA (which prevails over the undissociated one in surface water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 34 publications
(44 reference statements)
2
38
0
Order By: Relevance
“…Indeed, the significant decrease of A further photochemistry issue is that the decrease of DOC is expected to enhance as well the direct photolysis of organic compounds. Indeed, the chromophoric portion of DOM competes with other dissolved molecules for radiation absorption (Lam et al, 2003;Latch et al, 2003) and, in some cases, DOM can decrease the direct photolysis quantum yields of other substrates (Vione et al, 2010b). Figure 7 shows the PCA analysis (PC1 vs. PC2) of the data, grouped by season.…”
Section: Principal Components Analysis Resultsmentioning
confidence: 99%
“…Indeed, the significant decrease of A further photochemistry issue is that the decrease of DOC is expected to enhance as well the direct photolysis of organic compounds. Indeed, the chromophoric portion of DOM competes with other dissolved molecules for radiation absorption (Lam et al, 2003;Latch et al, 2003) and, in some cases, DOM can decrease the direct photolysis quantum yields of other substrates (Vione et al, 2010b). Figure 7 shows the PCA analysis (PC1 vs. PC2) of the data, grouped by season.…”
Section: Principal Components Analysis Resultsmentioning
confidence: 99%
“…Ding et al (2014) also reported that isopropanol is capable of quenching the direct photolysis of TCC even though OH• was not identified in their ESR data. Like Vione et al (2010) they attribute this anomaly to the scavenging of 3 TCC by the alcohol. Thus, it is conceivable that the complete quenching of the indirect pathway is caused by reaction between the excited state DOM and methanol.…”
Section: Figure 1 Triclocarban Measured Pseudo First Order Photo-degrmentioning
confidence: 98%
“…Recent research has demonstrated that simple alcohols are capable of quenching both OH• and reactive transients. Vione et al (2010) showed that isopropanol is capable of quenching 3 DOM involved in the indirect oxidation of 4-chloro-2-methylphenoxy-acetic acid (MCPA). They demonstrated by laser flash photolysis that the absorbance of the second transient species (presumably the triplet) is quenched significantly by approximately a factor of 3 at alcohol concentrations (25 mM) used in this and our previous study (Guerard et al, 2009) at pH = 7.8.…”
Section: Figure 1 Triclocarban Measured Pseudo First Order Photo-degrmentioning
confidence: 99%
“…Reactions of T 1 . Most processes of direct photolysis follow this route, which is favoured by the relatively long life of T 1 [3,4,6]. The conceptually simplest ways for triplet-state reactivity would be bond-breaking, rearrangement or reaction with the solvent, but less straightforward pathways are also possible.…”
Section: Direct Photolysismentioning
confidence: 99%